Crisis Management: Educational Administration in Southern Punjab, Pakistan During the Covid-19 Pandemic - Yumna; Urooj, Komal (iRASD Journal of Management, 2022)
The main purpose of the present dissertation is to investigate the impact of covid-19 crisis on educational administration of Schools of Management in Southern Punjab, Pakistan. The study adds to the literature by investigating the impact of crisis on administration and crisis management strategies formulated by the institutions along with their impact on institutions’ survival and recovery. A qualitative study is conducted to achieve research objectives and answer all formulated questions. Data was collected via semi structured interview of 8 representatives of different designations from these educational institutions. Thematic technique was applied to examine the collected data and to produce results based on them. Analyses showed that the COVID-19 crisis negatively influenced the financial health, education quality, exam quality and public perception about the institutions. the study revealed that on time decisions and proactive approach from the concerned bodies were important outcomes of the pre-COVID crisis experience. This experience enabled the different bodies like IT department, board of advance studies, academic council and syndicate to make on time decisions. The study also concluded that past crisis experiences also helped this institution to develop their strategies for survival and recovery. Moreover, development of IT infrastructure (LMS, Online Portals), Forming Health Emergency Teams, COVID-19 Protocols and Faculty Vaccination Drive were the prominent steps taken for the institute’s survival and recovery in COVID-19 breakout. Results showed that these strategies helped the institutes to survive during the pandemic situation.